Cardiac Fibrosis and Cardiac Fibroblast Lineage-Tracing: Recent Advances - Fu, Xing; Liu, Qianglin; Li, Chaoyang; Li, Yuxia; Wang, Leshan (Frontiers in Physiology, 2020)
Cardiac fibrosis is a common pathological change associated with cardiac injuries and diseases. Even though the accumulation of collagens and other extracellular matrix (ECM) proteins may have some protective effects in certain situations, prolonged fibrosis usually negatively affects cardiac function and often leads to deleterious consequences. While the development of cardiac fibrosis involves several cell types, the major source of ECM proteins is cardiac fibroblast. The high plasticity of cardiac fibroblasts enables them to quickly change their behaviors in response to injury and transition between several differentiation states. However, the study of cardiac fibroblasts in vivo was very difficult due to the lack of specific research tools. The development of cardiac fibroblast lineage-tracing mouse lines has greatly promoted cardiac fibrosis research. In this article, we review the recent studies exploring the detailed roles of fibroblasts in cardiac fibrosis using lineage-tracing and briefly discuss the translational potential of basic cardiac fibroblast researches.